2021
DOI: 10.3390/ijms22031432
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antiplatelet Agents on the Lipid Composition of Platelet Plasma Membrane: A Lipidomics Approach with Ticagrelor and Its Active Metabolite

Abstract: Lipids contained in the plasma membrane of platelets play an important role in platelet function. Modifications in the lipid composition can fluidify or rigidify the environment around embedded receptors, in order to facilitate the access of the receptor by the drug. However, data concerning the lipid composition of platelet plasma membrane need to be updated. In addition, data on the impact of drugs on plasma membrane composition, in particular antiplatelet agents, remain sparse. After isolation of platelet p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Data on the impact of plasma membrane fluidity in platelet activity are inconsistent. On the one hand, the antiplatelet drugs like ASA or ticagrelor rise the rigid of the platelets plasma membrane ( Watała and Gwoździński, 1993 ; Lagoutte-Renosi et al, 2021 ) and platelets from type 1 diabetic patients have increased fluidity of the membrane ( Mazzanti et al, 1997 ). On the other hand, platelet membrane is less fluid in patients who have hypertension, diabetes and also smoke ( Nanetti et al, 2008 ).…”
Section: Tannins and Plateletsmentioning
confidence: 99%
“…Data on the impact of plasma membrane fluidity in platelet activity are inconsistent. On the one hand, the antiplatelet drugs like ASA or ticagrelor rise the rigid of the platelets plasma membrane ( Watała and Gwoździński, 1993 ; Lagoutte-Renosi et al, 2021 ) and platelets from type 1 diabetic patients have increased fluidity of the membrane ( Mazzanti et al, 1997 ). On the other hand, platelet membrane is less fluid in patients who have hypertension, diabetes and also smoke ( Nanetti et al, 2008 ).…”
Section: Tannins and Plateletsmentioning
confidence: 99%
“…Lipidomics studies have reported that the lipid composition of the platelet membrane is crucial for the functioning of the cell. The lipid composition of the platelet membrane is responsible for a series of phenomena, such as the shape, curvature, and flexibility of the membrane and the flux of molecules through it [93,94]. It has also been shown that changes in the lipid composition of the platelet membrane induce structural and functional modifications such as activation, degranulation, and exocytosis processes [93,94].…”
Section: Lipid Compositionmentioning
confidence: 99%
“…(2) Skeaff and Holub [96] reported that, during platelet activation, thrombin, a platelet activator, causes a decrease of up to 45% in the content of phosphatidylinositol in the platelet plasma membrane [96]. (3) Lagoutte-Renosi et al [94] carried out a lipidomics study on resting platelet membranes. Their results showed that the membranes are constituted mainly by phosphatidylcholines (35.2 ± 0.8%), cholesterol (28.35 ± 0.7%), ether-linked phosphatidylethanolamines (10.40 ± 0.2%), sphingomyelins (7.26 ± 0.3%), phosphatidylserine (6.06 ± 0.1%), phosphatidylethanolamines (6.41 ± 0.1%), phosphatidylinositols (2.41 ± 0.03%), and ether-linked phosphatidylcholine (1.84 ± 0.04%) [94].…”
Section: Lipid Compositionmentioning
confidence: 99%
“…The actions of various agents and drugs can affect the compositions of plasma membranes and in the process change their functional properties. For example, certain antiplatelet drugs, such as ticagrelor, a membrane P2Y12 antagonist, and its active metabolite significantly increased platelet cholesterol and PC with short FA acyl chains, suggesting platelet membrane rigidification and modification of lipid-receptor interactions involved in ADP-induced platelet activation [37].…”
Section: Biological Membranes and Gplmentioning
confidence: 99%